HUBUNGAN STATUS GIZI TERHADAP MOTOR EDUCABILITY MURID SD MUHAMMADIYAH PERUMNAS KOTA MAKASSAR - Syahruddin Syahruddin; Mirfan Irfan Hasanuddin (Universitas Singaperbangsa Karawang, 2023)
This study aims to obtain answers to problems regarding the relationship between nutritional status and motor educability of students at SD Muhammadiyah Perumnas Makassar City. The research population used in this study were all students of SD Muhammadiyah Perumnas as many as 110 people. The type of research used in this study is the type of correlation, which means that all students in SD Muhammadiyah Perumnas Makassar City. Based on the results of the data analysis of nutritional status variables after being analyzed, it can be said that the nutritional status of the Muhammadiyah Perumnas Elementary School Makassar City as a whole can be said that their nutritional status is included in the